Vacation under the volcano - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1998)
Their magic tree house takes Annie and Jack to Pompeii just as Vesuvius is about to erupt, and they must find a Roman scroll before everything is covered with burning ash.
"A Stepping Stone book."
"RL: 2.2"--cover p. [4].
410
410
Accelerated Reader AR
Keywords: Time travel -- Fiction; Tree houses -- Fiction; Vesuvius (Italy) -- Eruption, 70 -- Fiction; Pompeii (Extinct city) -- Fiction